No more adoption rates! Looking for empowerment in agricultural development programmes - Bartlett, Andrew (2005)
The Plant Protection Department has responded to these developments by organising workshops for Farmer Trainers. This has led to further initiatives by IPM farmers. Mr Neupane and Mrs Bimauli are now members of the Jhapa IPM Association, an organisation that is run by farmers and which is linking up with similar associations in other Districts. The association in Jhapa plans and organises its own training activities, and negotiates the support required from the Department of Agriculture and Local Government Units.